Calcium intake and risk of colorectal cancer according to expression status of calcium-sensing receptor (CASR). Issue 8 (4th July 2017) - Yang, Wanshui; Liu, Li; Masugi, Yohei; Qian, Zhi Rong; Nishihara, Reiko; Keum, NaNa; Wu, Kana; Smith-Warner, Stephanie; Ma, Yanan; Nowak, Jonathan A; Momen-Heravi, Fatemeh; Zhang, Libin; et al.
Abstract : Objective: Although evidence suggests an inverse association between calcium intake and the risk of colorectal cancer, the mechanisms remain unclear. The calcium-sensing receptor (CASR) is expressed abundantly in normal colonic epithelium and may influence carcinogenesis. We hypothesized that calcium intake might be associated with lower risk of CASR-positive, but not CASR-negative, colorectal cancer. Design: We assessed tumour CASR protein expression using immunohistochemistry in 779 incident colon and rectal cancer cases that developed among 136 249 individuals in the Nurses' Health Study and Health Professionals Follow-Up Study. Duplication method Cox proportional hazards regression analysis was used to assess associations of calcium intake with incidence of colorectal adenocarcinoma subtypes by CASR status. Results: Total calcium intake was inversely associated with the risk of developing colorectal cancer (ptrend =0.01, comparing ≥1200 vs <600 mg/day: multivariable HR=0.75, 95% CI 0.60 to 0.95). For the same comparison, higher total calcium intake was associated with a lower risk of CASR-positive tumours (ptrend =0.003, multivariable HR=0.67, 95% CI 0.51 to 0.86) but not with CASR-negative tumours (ptrend =0.67, multivariable HR=1.15, 95% CI 0.75 to 1.78; pheterogeneity =0.06 between the CASR subtypes). The stronger inverse associations of calcium intake with CASR-positive but not CASR-negative tumours generally appeared consistent regardless of sex, tumour location and source of calcium. Conclusions: Our molecular pathological epidemiology data suggest a causal relationship between higher calcium intake and lower colorectal cancer risk, and a potential role of CASR in mediating antineoplastic effect of calcium.